Acute care handbook for physical therapists - Paz, Jaime C., 1966-; West, Michele P., 1969-; Panasci, Kathryn; Greenwood, Kristin Curry (St. Louis, Missouri : Elsevier, 2020)
Get all the essential information you need to effectively treat and manage patients in a complex acute care setting with Acute Care Handbook for Physical Therapists, 5th Edition. This easy-to-follow guide is the perfect resource to help any rehabilitation professional better understand and interpret hospital protocol, safety, medical-surgical'lingo,' and the many aspects of patient care in the hospital setting - from the emergency department to the intensive care unit to the general ward. And with extensively updated content reflecting the latest evidence-based information, this new fifth edition contains everything you need to succeed in today's fast-paced acute care environment.
Introduction -- Body systems -- Health conditions -- Interventions.
Includes bibliographical references and index.
Keywords: Acute Disease -- therapy; Critical Care; Physical Therapy Specialty; Handbook